Streptococcus sobrinus Antigens That React to Salivary Antibodies Induced by Tonsillar Application of Formalin-Killed S. sobrinus in Rabbits - Fukuizumi, Takaki (American Society for Microbiology, 2000)
We previously found that tonsillar application of antigen induces a strong antibody response to Streptococcus sobrinus in saliva and blood plasma. Rabbits immunized against S. sobrinus by tonsillar application were highly resistant to experimental dental caries triggered by oral inoculation of living S. sobrinus organisms with sucrose. In the present study, we examined the reaction of S. sobrinus antigens to the antibodies induced by the tonsillar application of S. sobrinus AHT-k in rabbits and compared them to those antibodies induced by intramuscular injection. In an enzyme-linked immunosorbent assay using ultrasonic fragments from mutans group streptococci, the saliva and blood plasma selectively reacted to S. sobrinus AHT-k (serotype g) and serologically related streptococci (serotypes a, d, and h) in the sixth week after tonsillar application, whereas the blood plasma in the sixth week after intramuscular injection reacted to the unrelated streptococci (serotypes b, c, e, and f) in addition to the aforementioned streptococci. The antibody reactivity induced after tonsillar application was not lost after treatment of the antigen with heat or proteinase digestion, whereas these treatments resulted in a 70% decrease of the antibody reactivity induced by intramuscular injection. The inhibition by haptenic sugars and the decrease in immunoreactivity by heat treatment and proteinase digestion suggested that 80% of the antibodies induced by tonsillar application reacted to saccharides. These saccharide antigens appeared to be involved in a specific reaction with S. sobrinus-specific streptococci and a selective reaction with serologically related streptococci. These antigens are probably involved in anticaries reactions in experimental dental caries.